Seismic evidence of fluid migration in the Barreirinhas basin, Central Brazilian Equatorial Margin - Guilherme Martins Delabrida; David Lopes de Castro; Moab Praxedes Gomes; José Paulo de Melo Goulart (Marine Geophysical Research, 2026)
The Brazilian Equatorial Margin (BEM) is an oblique-transform continental margin inherited from the Pangea breakup and the opening of the Equatorial Atlantic Ocean. Located in the central portion of the BEM, the Barreirinhas Basin is a frontier region with only three deep-water wells. Efforts have been made to understand its tectono-depositional evolution and potential for petroleum exploration. This study provides the first integrated characterization of fluid migration systems in the offshore Barreirinhas Basin, identifying and mapping seismic indicators, as well as connecting them with regional settings. We analyzed conventional 2D and 3D seismic reflection data, integrated with available well data. Additionally, seismic attributes (instantaneous amplitude, pseudo-relief, similarity, and chaos) were applied to enhance the interpretation of conventional seismic profiles. Our results show diverse fluid migration features, from deep strata to the seafloor, constrained in four main migration systems. Two systems are correlated to regional gravitational collapse. Fluid conduits, pockmarks, mounds, and faulted zones indicate focused fluid flow. A third system is developed in a region dominated by transform tectonics related to the Romanche Fracture Zone, in which dense fault networks are observed within a laterally extensive interval from the slope to the basin plain. The fourth system is located in a broad region of the basin plain, characterized by numerous seafloor mounds associated with fluid conduits and seismic indicators of hydrocarbon accumulation. These findings improve the knowledge about an underexplored basin and provide a foundation for the understanding of fluid migration systems and their implications, including marine processes and products, emplacement of igneous bodies, and hydrocarbon prospectivity.